Prevalence Of Tobacco Consumption and Associated Factors Among Adolescent School Children of Ahmedabad - Vyas, Monark J; Patel, Amul B (National Journal of Community Medicine, 2016)
Background: In Ahmedabad city, proportion of students currently using any tobacco products was 14.5%. The study was conducted to find out the prevalence of current and ever used tobacco consumption among the adolescent school children and also factor associated with tobacco consumption Methodology: A cross sectional study was conducted among 2000 students (12-19 years) of class VIII to XII from 532 schools of Ahmedabad city 1st January 2011 to 31 December 2011. Results: Prevalence of ever users of any tobacco products was 10.6%. Prevalence of current users of any tobacco products was 8.2%. The major factor found for initiating tobacco consumption among ever tobacco consumers was just for enjoyment & peer pressure (55%). Prevalence in students of Guajarati medium schools (12.1%) was higher than those who studied in English medium schools (7.9%). Conclusion: Tobacco use is still important risk behaviour among adolescent students. Prevalence of using smokeless tobacco product was more than prevalence in smokers. Evident gender difference (male predominance) was also observed in tobacco use.